Variasi Iklim dan Dinamika Kasus DBD di Indonesia: Systematic Review - Prayudhy Yushananta; Agus Setiawan; Tugiyono Tugiyono (Jurnal Kesehatan, 2020)
DHF is still a serious problem, especially in children in endemic countries. An estimated 3,6 billion people are at risk and 21,000 deaths each year. Indonesia, in 2018 there were 65,602 cases (IR=24,75 per 100,000 population), with the death of 467 people (CFR=0,71%), and 85.6% of districts in Indonesia reported dengue cases. The climate becomes one of the environmental factors that play a role in the number of cases. Google scholar is used as the main source for finding articles related to DHF and climate published during 2015-2019. The inclusion criteria set forth, are articles that must be published in international journals, published in 2015-2019, must discuss Indonesia, and must assess the effect of climate change on DHF. A total of 52 articles were found, but only 6 articles met the inclusion criteria. Using various analytical methods, all articles obtain climate variability related to the incidence of DHF, through vector abundance. The dynamics of DHF is a very complex system, so it is necessary to combine additional factors other than climate to predict it. The development of an early warning and monitoring system is important, in addition to strengthening the role of households in controlling DHF.